“Índio é índio onde quer que ele more”: uma etnografia sobre índios Potiguara que vivem na região metropolitana de João Pessoa - Lucena, Jamerson Bezerra (2016)
This dissertation aims to understand the networks of social relations elaborated by Potiguara indigenous in João Pessoa’s metropolitan area and how it’s produce interactions in the urban spatiality involving the cities of Bayeux, Santa Rita and João Pessoa, Paraiba. This spatial dynamic causes interethnic contacts with various social actors, educational institutions and indigenous agencies such as FUNAI and SESAI, whose subsequent relations generate joints, disagreements, conflicts and new forms of interactivity. By these flows of people between indigenous territory and city, the Potiguara move from one place to another dynamically, with cooperation from that one living in town to other one that stay living in the village, in accordance to their feelings of belonging and moral recognition (Cardoso de Oliveira, 2006), being ethnic boundaries stressed in certain situations. The Potiguara brought their experiential baggage from village and pass through the cities, building their networks from vicinal and friendship relations conceived by kindness in a field of mutal help, and by their relatives who are "scattered" by the urban space. And this relationship, kinship and friendship ties will strengthen and producing ramifications beyond the boundaries of urban spatiality. Therefore, in the interactions provided by the networks of social relations, reciprocity was established as a closing link of friends, family and relatives, creating a continuous process of production and reproduction of cultural materials that reverberate their feelings of belonging. This study is focused on two empirical cases that the Dona Maria das Neves Santana and Jose Ciriaco Sobrinho (Capitão) that are located in the cities, namely, Bayeux and Joao Pessoa, respectively.Studying both cases, we seeking reconstitute their social relationship networks. And their arrivals are motivated by different circumstances, in coming to a family and in the other case the search for work to acquire financial stability and consequently build family. Besides these two cases also I focused my attention to the social relations of six indigenous youth Potiguara studying at the Federal University of Paraíba (UFPB), that across the tome built a solidarity network in the capital, intensifying, when necessary, the ethnic belonging.